Modules with unique closure relative to a torsion theory. III - Dogruoz, S.; Harmanci, A.; Smith, P.F. (Український математичний журнал, 2014)
We continue the study of modules over a general ring R whose submodules have a unique closure relative to a hereditary torsion theory on Mod-R. It is proved that, for a given ring R and a hereditary torsion theory τ on Mod-R, every submodule of every right R-module has a unique closure with respect to τ if and only if τ is generated by projective simple right R-modules. In particular, a ring R is a right Kasch ring if and only if every submodule of every right R-module has a unique closure with respect to the Lambek torsion theory. Продовжено вивчення модулів над загальним кільцем R, субмодулі якого мають єдине замикання відносно спадкової теорії скруту на Mod-R. Доведено, що для заданих кільця R та спадкової теорії скруту τ на Mod-R кожний субмодуль кожного правого R-модуля має єдине замикання відносно τ тоді i тільки тоді, коли τ породжується проективними простими правими R-модулями. Зокрема, кільце R є правим кільцем Каша тоді i тільки тоді, коли кожний субмодуль кожного правого R-модуля має єдине замикання відносно теорії скруту за Ламбеком.